Antioxidant Activity of Carotene-rich Sweet potato Extracted with an Hexane-Ethanol Solvent mixture - Nareswari, Nadia; Estiasih, Teti; Murtini, Erni Sofia (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
<p style=